Harmful macroalgal blooms (HMBs) in China's coastal water: Green and golden tides - Xiao, Jie; Wang, Zongling; Liu, Dongyan; Fu, Mingzhu; Yuan, Chao; Yan, Tian (Harmful algae, 2021)
•Harmful macroalgal blooms (HMBs) are increasingly occurring over a wide geographic range along the China's coasts.•The distinct genesis and blooming dynamics of three HMBs are summarized and compared.•Countermeasures have been implemented to effectively abate the massive green tide in the Yellow Sea.•The blooming mechanism of golden tides and ecological impacts of HMBs need to be further investigated. Harmful macroalgal blooms (HMBs) have been increasing along China's coasts, causing significant social impacts and economic losses. Besides extensive eutrophication sustaining coastal seaweed tides, the stimuli and dynamics of macroalgal blooms in China are quite complex and require comprehensive studies. This review summarizes the distinct genesis, development and drifting patterns of three HMBs that have persistently occurred in China's coastal waters during recent years: transregional green tides of drifting Ulva prolifera in the Yellow Sea (YS), local green tides of multiple suspended seaweeds in the Bohai Sea and large-scale golden tides of pelagic Sargassum horneri in the YS and East China Sea. While specific containment measures have been developed and implemented to effectively suppress large-scale green tides in the YS, the origin and blooming mechanism of golden tides remain unclear due to lack of field research. With the broad occurrence of HMBs and their increased accumulation on beaches and coastal waters, it is necessary to investigate the blooming mechanism and ecological impacts of these HMBs, especially with the growing stresses of climate change and anthropogenic disturbances.